Evaluation of the ecotoxicological effects of UV filters on freshwater planarian Girardia tigrina - Rolo, Patrícia Inês Graça (2023)
UV filters are used in various products, ranging from industrial settings, where they prevent the photodegradation of materials, to human consumption through personal care products designed to shield the skin from UV rays. They are currently classified as contaminants of emerging concern as they present endocrine-disrupting capabilities, impacting the development and reproduction of the organisms. Their occurrence in freshwater environments has been documented, and high concentrations have been found in areas with intensified recreational activities and wastewater discharges. Organic UV filters are expected to accumulate in sediments when introduced in aquatic environments due to their physical-chemical characteristics, increasing the exposure to benthic andepibenthic organisms such as planarians. Freshwater planarians' unique characteristics, such as their ability for regeneration and the similarity of their nervous system to that of vertebrates, have demonstrated their utility in the most varied scientificfields. These organisms are also sensitive to environmental contaminants and suited for assessing several ecotoxicological endpoints. Therefore, this thesis aimed to assess the sensitivity of Girardia tigrinato two organic UV filters, Benzophenone-3 (BP-3) and Enzacamene (4-MBC), by evaluating their effects on survival, behaviour (through locomotion), cephalic regeneration after decapitation and biochemical endpoints related to oxidative stress and damage, and neurotoxicity. Lethal effects were registeredin planarians exposed to BP-3 and 4-MBC with similar estimated LC₅₀ similar among compounds in the low mg/L range (1483 µg/L and 1653 µg/L). Sublethal concentrations of both compounds delayed cephalic regeneration, with 4-MBC presenting the highest impact on this endpoint. Exposure to 4-MBC also induced impairments in the locomotion of planarians, although no effects were observed after BP-3 exposure. Additionally, both compounds induced oxidative stress in G. tigrina, eliciting antioxidant responses (increase intotal glutathione in both compounds and Glutathione S-Transferase for 4-MBC). However, lipid damage was only observed with BP-3 exposure. Both UV filters decreased AChE activity, indicating possible neurotoxic effects, which may affect G. tigrina'slocomotor capacity and regeneration capabilities. In conclusion, the resulting data demonstrates these two organic UV filters' toxicity and potentially deleterious effects on the freshwater planarian, with similar toxicity among compounds, even if at concentrations higher than environmentally reported ones. Given the high concentrations already reported in freshwater ecosystems and their expected rise over the years, we still warn of the risk they represent to the aquatic environment.